rTMS for the treatment of psychiatric disorders: a review about training courses and materials and the presentation of the training materials of the German Society for Brain Stimulation in Psychiatry - Martin Schecklmann; Wolfgang Strube; Wolfgang Strube; Katrin Sakreida; Ulrike Vogelmann; Ulrike Vogelmann; Christiane Licht; Andreas Reissmann; Stefanie Dierkes-Möller; Roberto Goya-Maldonado; Bernhard Kis; Michael Landgrebe; et al. (Frontiers in Psychiatry)
There is an increasing interest in the treatment of mental disorders such as depression using repetitive transcranial magnetic stimulation (rTMS). Treatment guidelines for the application of rTMS are available, but they focus primarily on scientific evidence for efficacy and tolerability. Other aspects that are relevant for the training of practitioners, such as implementation in the national health system as well as organizational, formal, and practical aspects, are not covered in detail in these guidelines. Here, we present an overview of German rTMS courses and present training materials for the hands-on workshop of the German Society for Brain Stimulation in Psychiatry [Deutsche Gesellschaft für Hirnstimulation in der Psychiatrie (DGHP) e.V.] in German and English as an example. Publishing national standard operating procedures is important in order to harmonize rTMS practice all over the world.